Penerapan Analisis Swot terhadap Strategi Pengelolaan Bumdes Mitra Sejahtera dalam Peningkatan Ekonomi Masyarakat Studi Kasus Desa Tempuran Kecamatan Ngluyu Kabupaten Nganjuk Jawa Timur - Rodiatuz Zahro, Dewi Anifa; Zaini, Ahmad Afan; Munir, Akhmad Sirojudin (Al-Muzdahir : Jurnal Ekonomi Syariah, 2024)
The management of BUMDes Mitra Sejahtera aims to act as a driving force for village-level local development. The management of Mitra Sejahtera BUMDes is based on potential needs, village capacity, increasing village community income with the aim of improving the community's economy based on cooperative, emancipatory and participatory principles from the community. The discussion of this research aims to analyze the SWOT method, challenges to the Mitra Sejahtera BUMDes manager, with the aim of being able to overcome all the problems that will later become obstacles to the glory of Mitra Sejahtera BUMDes by using the SWOT method. The research methodology used in this study is a qualitative approach, namely by interviewing the community, the head of the Mitra Sejahtera BUMDes, the village head. In order to find out the management carried out by the Mitra Sejahtera BUMDes which is used to improve the community's economy. This discussion gets The result is that Mitra Sejahtera BUMDes has many opportunities to improve the community's economy, has competent leaders and has good planning and management which is very necessary for the progress of Mitra Sejahtera BUMDes. the research that has been done is the application of swot analysis to the prosperous partner BUMDes management strategy in improving the community's economy. where people participate and cooperate with each other. In the management of BUMDes where HR is the determinant of the running of a Mitra Sejahtera BUMDes, it is necessary to provide education to the community and education to managing HR. With a SWOT analysis, it can make it easier and know where to study events and threats in the future, anticipate losses if an obstacle occurs and with this analysis it can be avoided and applied for the good and welfare of society and can help people in need